Evaluasi Keberlanjutan Mata Pencaharian Nelayan Gillnet Melalui Pendekatan Teknik Rapfish - Belvi Vatria (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2020)
Small-scale fisheries development will be more effective if it focuses on strengthening fishermen's livelihoods. The main focus of the sustainable livelihood approach is to improve livelihoods by bringing together all elements of development for poverty alleviation. However, the problem that arises is that the implementation of the evaluation of the sustainability of small-scale fisheries development becomes difficult to analyze when faced with multi-dimensional conditions that affect it. Especially when faced with the condition of integrating all ecological, human, physical, financial, social, economic, and institutional data. Therefore, we need an evaluation technique that can integrate all the information comprehensively. One of the sustainability evaluation techniques with a quantitative approach is the Rapfish technique. The purpose of this study was to evaluate the sustainability of the livelihoods of Gillnet fishermen in Kayong Utara Regency, West Kalimantan Province through the Rapfish technique approach. The evaluation results show that the sustainability status of the livelihoods of Gillnet fishermen represented by the captain and crew is quite sustainable, although, with different MDS scores, they are still in the same range. Eleven sensitive attributes were found that influenced the sustainability status, namely: the threat of natural disasters, other natural resources, expected education, number of children, ice conditions, added value processing, remittances from migrants, social structure, leadership, trust/honesty, and support. /participation. This sensitive attribute is a driving factor or an inhibiting factor for the sustainability of the livelihoods of Gillnet fishermen